The Professional Culture of Teachers in Secondary Education: A Biographical Study - Rivas Flores, José Ignacio; Sepulveda Ruiz, Maria Del Pilar; Munoz, Pilar Rodrigo (Education Policy Analysis Archives, 2005)
This work discusses the "voices" of teachers working "at the chalk face." We are interested in learning what teachers think and how they behave. Therefore, we conducted our research about their working conditions. We also developed teachers" professional biographies to learn how these educators construct concepts and practices related to their profession and what constitutes their "professional culture". We understand that thie professional culture characterizes teachers" professional frameworks and choices; therefore, any attempt to successfully promote an educational reform, must understand and pay attention to the "professional culture."